PENGARUH PASOKAN, PENENTUAN HARGA DAN INSENTIF TERHADAP KEPUASAN AGEN PT. COCA – COLA WILAYAH SEMARANG BARAT (Students' Journal of Economic and Management, 2015)
This research is a study that evaluated the effects of supply, pricing and incentives to the agent satisfaction PT. Coca - Cola West Semarang. The samples used in this study were 44 respondents. The sampling technique used in the form of a random sample, or by selecting a portion of the total population and scrambled it to be sampled. Data collected was tested first using validity and reliability in order to obtain valid and reliable results that can be used in subsequent testing. Subsequent analysis the authors use multiple linear regression testing to clarify the relationship between the independent and dependent variables. The result is a variable supply, pricing, and incentives positive and significant impact on satisfaction agents. Variables that have the greatest influence is variable pricing of this was due to the variable pricing has the largest beta value when compared with variable supply and incentives. Keywords: Supply, Pricing, Incentives and Satisfaction